EFL Learners’ Perceptions of the Use of Think–Pair–Share in their Viewing Activities during Transactional Conversation Course at an Undergraduate English Education Program - Ayuri Rafikatul Husna; Puji Astuti (Universitas Islam Negeri Palopo, 2026)
This study explores how EFL learners perceive the use of Think–Pair–Share (TPS) in viewing activities within a Transactional Conversation course. Although TPS is commonly used in EFL settings, its role in viewingbased learning from learners’ perspectives remains limited. This study employed a qualitative descriptive design, involving 20 learners who completed open-ended questionnaires and six of them were interviewed for deeper insights. The data were analyzed using thematic analysis. The findings highlight four key themes: perceived effectiveness, learning process, engagement and interaction, and implementation challenges. TPS was found to increase engagement, support understanding through peer discussion, and encourage active participation during viewing tasks. However, challenges such as limited time, unequal participation, and language difficulties were also reported. These findings suggest that TPS can make viewing activities more interactive and meaningful, but its success depends on thoughtful implementation, including appropriate time allocation, balanced group interaction, and support for learners’ language development.